2020
DOI: 10.3390/jcm9020418
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Events Are Independently Associated with Liver Stiffness in Patients with Fontan Circulation

Abstract: Background: Thromboembolism (TE) and Fontan-associated liver disease (FALD) are common and lead to significant morbidity in Fontan circulations. Risk factors for TE and the potential link between TE and FALD are not well understood. The objective of this study was to evaluate the association between TE and the severity of FALD based on radiologic liver stiffness. Methods: Using a retrospective cohort study design, 85 Fontan patients (aged 27.7 ± 8.2 years) who had liver stiffness measurement were included. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A very recent study showed that LS was significantly higher in Fontan patients with portal hypertension (5.2 vs. 4.2 kPa, p = 0.03) and Fontan failure (5.1 vs. 4.2 kPa, p = 0.01), and concluded that “elevated MRE‐derived LS is associated with worse hemodynamics, liver enzymes and clinical outcomes in Fontan patients.” 79 The same authors also showed that thromboembolic events in patients with Fontan circulation are independently associated with LS (Figure 9). 80 …”
Section: Disease‐specific Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent study showed that LS was significantly higher in Fontan patients with portal hypertension (5.2 vs. 4.2 kPa, p = 0.03) and Fontan failure (5.1 vs. 4.2 kPa, p = 0.01), and concluded that “elevated MRE‐derived LS is associated with worse hemodynamics, liver enzymes and clinical outcomes in Fontan patients.” 79 The same authors also showed that thromboembolic events in patients with Fontan circulation are independently associated with LS (Figure 9). 80 …”
Section: Disease‐specific Resultsmentioning
confidence: 99%
“…79 The same authors also showed that thromboembolic events in patients with Fontan circulation are independently associated with LS (Figure 9). 80 Biliary Atresia Biliary atresia (BA) is a progressive fibroinflammatory process that causes obliteration of the extra-and intra-hepatic biliary tree and that clinically presents during the first few weeks of life with persistent jaundice and elevated conjugated bilirubin. Historically, the diagnosis of BA has been challenging, often relying on some combination of B-mode ultrasound, hepatobiliary scintigraphy, liver biopsy, and intraoperative cholangiography.…”
Section: Nafld/nashmentioning
confidence: 99%
“…The existing literature suggests that indeed the most common risks to the mother in the Fontan pregnancy are of arrhythmias, heart failure and thromboembolic or bleeding events [15][16][17]. Overall, however, these risks are relatively low and patients have been reported as having been managed effectively and without long-term sequelae [18,19].…”
Section: Maternal Complicationsmentioning
confidence: 99%
“…Pregnancy is a pro-thrombotic state. It has been known for many years that the Fontan operation and all its modifications also increases the risk of thromboembolism [15][16][17]. The reasons for this are complex.…”
Section: Thromboembolismmentioning
confidence: 99%
“…In the critically ill ACHD patient, examination of hepatic physiology can help define risk. For example, in Fontan patients, thromboembolic events may be associated with liver stiffness [69]. The Model for End-stage Liver Disease eXcluding INR (MELD-XI) score was originally developed to assess cirrhotic patients and has prognostic value for heart failure patients as well.…”
Section: Hepatic Dysfunctionmentioning
confidence: 99%